Cancer immunotherapy in routine cost‐effective cancer care? - Sir Marc Feldmann (EMBO Molecular Medicine)
Abstract Therapy‐triggered autoimmunity and inflammation in many cancer patients, as well as treatment costs, hamper the success of cancer immunotherapy. The study by Pfeiffer et al in this issue of EMBO Molecular Medicine constitutes a clear step towards a more simple, scalable and affordable approach in generating in situ T cells reprogrammed with chimeric antigen receptors (CARs) (Pfeiffer et al, 2018).